Biocompatible Size-Defined Dendrimer-Albumin Binding Protein Hybrid Materials as a Versatile Platform for Biomedical Applications - Maly, Jan; Stanek, Ondrej; Frolik, Jan; Maly, Marek; Ennen, Franka; Appelhans, Dietmar; Semeradtova, Alena; Wrobel, Dominika; Stofik, Marcel; Knapova, Tereza; Kuchar, Milan; Stastna, Lucie Cervenkova; et al. (Macromolecular bioscience, 2016)
For the design of a biohybrid structure as a ligand-tailored drug delivery system (DDS), it is highly sophisticated to fabricate a DDS based on smoothly controllable conjugation steps. This article reports on the synthesis and the characterization of biohybrid conjugates based on noncovalent conjugation between a multivalent biotinylated and PEGylated poly(amido amine) (PAMAM) dendrimer and a tetrameric streptavidin-small protein binding scaffold. This protein binding scaffold (SA-ABDwt) possesses nM affinity toward human serum albumin (HSA). Thus, well-defined biohybrid structures, finalized by binding of one or two HSA molecules, are available at each conjugation step in a controlled molar ratio. Overall, these biohybrid assemblies can be used for (i) a controlled modification of dendrimers with the HSA molecules to increase their blood-circulation half-life and passive accumulation in tumor; (ii) rendering dendrimers a specific affinity to various ligands based on mutated ABD domain, thus replacing tedious dendrimer-antibody covalent coupling and purification procedures.
Keywords: biohybrid structures; binding domain proteins; Cell Line; epitelové buňky; Rats; sekvence aminokyselin; Models, Molecular; ligandy; Protein Binding; Nanoparticles; Streptavidin; Streptavidin-biotin conjugations; sérový albumin; Epithelial Cells; biotinylace; lékové transportní systémy; Polyethylene Glycols; Dendrimers; Streptomyces; HSA; krysa rodu Rattus; polyethylenglykoly; streptavidin; Bacterial Proteins; Serum Albumin; dendrimery; Biotin; Ligands; Escherichia coli; molekulární modely; Gene Expression; zvířata; Humans; Amino Acid Sequence; Recombinant Fusion Proteins; vazba proteinů; rekombinantní fúzní proteiny; nanočástice; biotin; exprese genu; polyaminy; buněčné linie; Drug Delivery Systems; PAMAM dendrimer; bakteriální proteiny; Biotinylation; Polyamines; lidé; Animals